ANALISIS LEVEL KEMAMPUAN PEMECAHAN MASALA MATEMATIKA SISWA PADA PELAKSANAAN PEMBELAJARAN SECARA DARING DI SMK N 1 SOSORGADONG - Dostika Ashari Simatupang; Eva Yanti Siregar; Sinar Depi Harahap (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
Abstract This study aims to analyze the level of students' mathematical problem solving abilities in the implementation of online learning at SMK N 1 Sosorgadong. This research approach is descriptive qualitative. The research subjects were 14 students. Interviews and tests were used in data collection and triangulation techniques were used in analytical techniques. The results showed that the average mathematical problem solving ability of students was 70.23 (medium category). In conclusion, students' mathematical problem solving abilities in the implementation of online learning at SMK N 1 Sosorgadong include students having the ability to plan, monitor problem solving, and recheck answers.